Developing Digital Game E-Calf As Self-Directed Learning Media For The First Grade Students Of Elementary School At SD Lab Undiksha Singaraja - I. W. A. K., Yuda (LPPM Undiksha, 2018)
This research aimed to develop digital game e-CALF as self-directed learning media. The subject of this research was 23 students (30%) of first grade students at SD Lab UNDIKSHA Singaraja. The design of this research adapted to research and development ADDIE model proposed by Romiszowski (1996). Since, it was still a prototype product, there were only three procedures used namely Analyze, Design and Development. In collecting the data, some instruments were used to conduct this research. There were observation sheet, teacher’s interview guide, expert judgment rubrics, students’ questionnaire, and syllabus analysis. In the end of this research, there was a prototype product named e-CALF as self-directed learning media in form of application. The result of this research is digital game that is developed based on syllabus analysis and the students’ needs. It is developed based on four topics namely; family, things in the classroom, fruits, and vegetables. Each topic consists of six sheets; there are two sheets about the vocabulary, two sheets about filling the blank text, and two sheets about comprehension text with the questions. Based on the result of expert judgment rubrics, it is found that e-CALF is categorized as excellent media. Thus, this prototype product is proper to use for learning English for first grade students